2008
DOI: 10.1158/0008-5472.can-08-0644
|View full text |Cite
|
Sign up to set email alerts
|

Role of Acetylation and Extracellular Location of Heat Shock Protein 90α in Tumor Cell Invasion

Abstract: Heat shock protein (hsp) 90 is an ATP-dependent molecular chaperone that maintains the active conformation of client oncoproteins in cancer cells. An isoform, hsp90A, promotes extracellular maturation of matrix metalloproteinase (MMP)-2, involved in tumor invasion and metastasis. Knockdown of histone deacetylase (HDAC) 6, which deacetylates lysine residues in hsp90, induces reversible hyperacetylation and attenuates ATP binding and chaperone function of hsp90. Here, using mass spectrometry, we identified seven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
229
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(253 citation statements)
references
References 47 publications
15
229
4
1
Order By: Relevance
“…4A). Although human Hsp90 is also reported to be acetylated (22), the sites of acetylation do not coincide with those for PfHsp90 found in this study. Interestingly, the interaction site of Hsp90 with co-chaperones p23 and Aha1, as reported in yeast, was found to coincide with Lys-426 of PfHsp90 (supplemental Fig.…”
Section: Pfhsp90 Is Hypersensitive To Ga-mediated Inhibition Of Itscontrasting
confidence: 93%
“…4A). Although human Hsp90 is also reported to be acetylated (22), the sites of acetylation do not coincide with those for PfHsp90 found in this study. Interestingly, the interaction site of Hsp90 with co-chaperones p23 and Aha1, as reported in yeast, was found to coincide with Lys-426 of PfHsp90 (supplemental Fig.…”
Section: Pfhsp90 Is Hypersensitive To Ga-mediated Inhibition Of Itscontrasting
confidence: 93%
“…Furthermore, the binding affinities of Hsp90 for inhibitors can be influenced by its interactions with co-chaperones [17,22,[37][38][39][40][41], which in turn may be modulated by posttranslational modifications of Hsp90 (see for example refs. [42][43][44]). Since we had found that the Hsp90 co-chaperone p23 directly protects Hsp90 from binding inhibitors [22], we did introduce the Pf p23 ortholog into yeast.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a key co-chaperone of Hsp90 that is involved in the maturation, stabilization, activation and function of oncogenic proteins [12] . Thus, disrupting the AHA1/Hsp90 complex would cause the depletion of client proteins and kinase clients that are involved in tumor cell proliferation and survival, as well as in all the hallmark traits of malignancy.…”
Section: Original Articlementioning
confidence: 99%
“…The protein concentration in the cell lysates was quantified using the Quick Start Bradford Dye Reagent (Bio-Rad), and the samples were subjected to SDS-PAGE. Western blot analysis was performed as described previously [12] . β-Actin was used as a loading control.…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation